Antioxidant effects of American ginseng berry extract in cardiomyocytes exposed to acute oxidant stress - Shao, Zuo-Hui; Xie, Jing-Tian; Vanden Hoek, Terry L.; Mehendale, Sangeeta; Aung, Han; Li, Chang-Qing; Qin, Yimin; Schumacker, Paul T.; Becker, Lance B.; Yuan, Chun-Su (Biochimica et biophysica acta, 2004)
It is postulated that antioxidant properties of American ginseng root mediate its cardioprotective actions. The antioxidant capabilities of the American ginseng root have been demonstrated previously, however, the berry of the American ginseng has not yet been evaluated. In this study, we tested the American ginseng berry extract (AGBE) for its antioxidant effects in cell-free chemical systems using H 2O 2/FeSO 4 to generate hydroxyl radicals which were measured by a fluorescent probe, 2′, 7′-dichlorofluorescin diacetate (DCFH/DA). Xanthine/xanthine oxidase was used to generate superoxide anion, which was measured by a fluorescent probe dihydroethidium (DHE). We found that AGBE decreased fluorescence significantly, suggesting that AGBE scavenges oxygen free radicals. We further tested whether AGBE (0.1–1 mg/ml) can protect cardiomyocytes from oxidative injury induced by exogenous or endogenous oxidants. Cells were exposed to either H 2O 2 or antimycin A (a mitochondrial electron transport chain site III inhibitor that augments mitochondrial oxidant production). The resulting oxidant stress was measured using DCFH/DA and the cell death was assessed using propidium iodide staining. Pretreatment with AGBE (1 mg/ml) significantly attenuated DCF fluorescence by 49% or 85% and reduced cell death by 59% or 63% in cells exposed to H 2O 2 or antimycin A, respectively. When the effects of extracts from berry and root of American ginseng were compared in cardiomyocytes exposed to antimycin A, we observed that AGBE conferred greater antioxidant protection at the same dose. We conclude that AGBE is a potent antioxidant that protects cardiomyocytes against oxidant-mediated injury and this protection is partly mediated by its free radical scavenging properties.